Analisa Tingkat Pemahaman Adat Istiadat Masyarakat Kenagarian Kinari Dengan Konsep Fuzzy Logic - Saputra, Dhio; Wisky, Irza Arief (Jurnal Inovasi Teknik Informatika, 2024)
Kinari Nagari is one of the nagari in the Bukit Sundi sub-district, Solok regency which has Minangkabau customs that are still sustainable in the midst of community life, Kinari Nagari is also known as Nagari a thousand one rumah gadang with the customary application of basandi sarak, sarak basandi Kitabullah, which means community life is inseparable from harmony between customs and religion, kinari nagari has a tradition that is still thick, everything is seen in the daily lives of the people who still apply customary rules and norms of Minangkabau, which are seen in the way of communication, daily behavior, the way to dress it all is written in the customary rules that exist in the village. Customs are cultural behaviors and rules that have been tried to be implemented in the community, with the existence of customs can have an impact on the behavior of the kinari nagari community. This research was conducted to analyze the level of understanding of the kinari dancarian community customs. This research was conducted with the concept of fuzzy logic based on artificial intelligent (AI).